The Role of Internal and External Audits in Corporate Governance Structure a Case Study of Hotels in Ho-Volta Region - Kortsu-Mensah, F.Y. (University of Ghana, 2019)
The purpose of this study is to determine the roles of internal and external audits in corporate governance structure. This study was conducted in ten hotels in Ho, the Volta Regional Capital. In this research, the stratified sampling method was used in attaining the sample size by concentrating on the various units of the selected Hotels for the study. This enabled the researcher to highlight differences between groups in a population which ensured different views obtained on the subject matter and also allowed for 100% response rate. The research design used was mixed method. Qualitative and quantitative data were analyzed by using the Statistical Package for the Social Science (SPSS). Chi-Square Test was performed to establish whether there is a relationship among the variables understudied with a null hypothesis of corporate governance which is independent of internal and external audit. The results of the analysis show that the significances of these tools are clear as these tools coordinate in providing assurance, enhancing and improving internal control systems, risk assessments and management, enhancing financial reporting, ensuring funds are spent as expected as well as enhancing good corporate governance by providing oversight, foresight and insight roles in relation to compliance to law and regulations both internal and external. It was also found that, even though management is aware of these significance and the expectations of stakeholders, they are reluctant to acquire and use these services. The internal and external audits as demonstrated in this study are two other tools that can help to protect these investments when acquired and allowed to function as expected. If management is reluctant of acquiring these services, it could me that either, they are not fully aware of the significance these tools bring or they intentionally do not want to use them because of their own personal benefits.
MSc.
Keywords: Audit; Corporate Governance Structure; Ho-Volta Region